The antimicrobial effects of the alginate oligomer OligoG CF-5/20 are independent of direct bacterial cell membrane disruption - Pritchard, Manon F. (Sci Rep, 2017)
Concerns about acquisition of antibiotic resistance have led to increasing demand for new antimicrobial therapies. OligoG CF-5/20 is an alginate oligosaccharide previously shown to have antimicrobial and antibiotic potentiating activity. We investigated the structural modification of the bacterial cell wall by OligoG CF-5/20 and its effect on membrane permeability. Binding of OligoG CF-5/20 to the bacterial cell surface was demonstrated in Gram-negative bacteria. Permeability assays revealed that OligoG CF-5/20 had virtually no membrane-perturbing effects. Lipopolysaccharide (LPS) surface charge and aggregation were unaltered in the presence of OligoG CF-5/20. Small angle neutron scattering and circular dichroism spectroscopy showed no substantial change to the structure of LPS in the presence of OligoG CF-5/20, however, isothermal titration calorimetry demonstrated a weak calcium-mediated interaction. Metabolomic analysis confirmed no change in cellular metabolic response to a range of osmolytes when treated with OligoG CF-5/20. This data shows that, although weak interactions occur between LPS and OligoG CF-5/20 in the presence of calcium, the antimicrobial effects of OligoG CF-5/20 are not related to the induction of structural alterations in the LPS or cell permeability. These results suggest a novel mechanism of action that may avoid the common route in acquisition of resistance via LPS structural modification.